1950
DOI: 10.1103/physrev.80.230
|View full text |Cite
|
Sign up to set email alerts
|

The Electrical Conductivity of an Ionized Gas

Abstract: The interaction term in the Boltzmann equation for an ionized gas is expressed as the sum of two terms: a term of the usual form for close encounters and a diffusion term for distant encounters. $ince distant encounters, producing small deflections, are more important than close encounters, consid'eration' of only the diffusion term gives a reasonably good approximation in most cases and approaches exactness as the temperature increases or the density decreases. It is shown that in evaluating the coefBcients i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
200
0
1

Year Published

1956
1956
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 412 publications
(212 citation statements)
references
References 10 publications
9
200
0
1
Order By: Relevance
“…The description is based on the Frost mixture rule. 39 In the limit of a fully singly ionized plasma, this mixture rule converges to the Spitzer-Härm value SH of 40 with the electron temperature T e in kelvins and ln ⌳ the Coulomb logarithm. For a nonfully singly ionized plasma, the collisions between electrons and neutrals, viz., N and N 2 , cause the conductivity to be lower.…”
Section: ͑13͒mentioning
confidence: 84%
“…The description is based on the Frost mixture rule. 39 In the limit of a fully singly ionized plasma, this mixture rule converges to the Spitzer-Härm value SH of 40 with the electron temperature T e in kelvins and ln ⌳ the Coulomb logarithm. For a nonfully singly ionized plasma, the collisions between electrons and neutrals, viz., N and N 2 , cause the conductivity to be lower.…”
Section: ͑13͒mentioning
confidence: 84%
“…The laser energy deposition via inverse bremsstrahlung is calculated with a three-dimensional ray tracing package. The electron thermal conduction is treated by the Spitzer-Härm model [30,31]with a flux limiter [32] which is usually taken as 0.08 in our simulations. The thermodynamic quantities are derived either from the ideal gas model or from data of realistic equation of state.…”
Section: Code and Modelmentioning
confidence: 99%
“…The temperature gradient r e is estimated numerically from the ion line data. The Knudsen number 2k e r log e (Guio et al, 1998) where k e is the electron mean free path, is a parameter used in the Spitzer function (Cohen et al, 1950;Spitzer and HaÈ rm, 1953) to represent the electron ambient distribution function in presence of a temperature gradient.…”
Section: The Datamentioning
confidence: 99%
“…This heat¯ow correction term behaves as an additional mean Doppler velocity that arti®cially increases the di erence of the Doppler shifts of the plasma lines. Guio et al (1998) showed that the heat¯ow e ect was underestimated for UHF radars by comparing the heat¯ow approximation of the dispersion relation with a full numerical estimation of the dielectric response function using the Spitzer velocity distribution for a plasma with a temperature gradient (Cohen et al, 1950;Spitzer and HaÈ rm, 1953). It was also shown that for VHF radars, suprathermal electrons would contribute to modify the dielectric response function and thus the Doppler frequency of the plasma lines.…”
Section: Introductionmentioning
confidence: 99%